Power and influence mapping in Ghana's agricultural adaptation policy regime - Sova, Chase; Thornton, Thomas F.; Zougmoré, Robert B.; Helfgott, Ariella E.S.; Chaudhury, Abrar S. (Informa UK Limited, 2017)
Debates around the design and content of climate change adaptation policies are shaped, in part, by the power and influence of actors within an adaptation regime. This paper applies a power-mapping technique, Multilevel Stakeholder Influence Mapping (MSIM), to stakeholders in Ghana's agricultural adaptation policy regime. The method provides a quantitative influence score and visual map for actor groups active-in or affected-by the policy process, from the differentiated perspectives of national, regional, and local-level respondents. MSIM, as applied here, seeks to determine the underlying power structure of the adaptation regime and provides insight in to two key power-laden themes: stakeholder participation and multilevel institutional design. Results indicate that when taken collectively (the views of national, regional and local respondents combined) Ghana's adaptation regime is considered bipolar and elite-centred in its power distribution. A distinguishable ‘adaptation establishment’ or dominant group of power holders made up of technical government and international agencies can be identified. Meanwhile, political groups, the private sector, civil society, and universities are considered to wield substantially less power in the regime. Differentiated perspectives (i.e. national, regional or local respondents alone) reveal that several potential cross-level bridging institutions are not considered influential at all operational levels. Farmers, traditional authorities, and the District Assembly, for example, are all considered highly influential from the perspective of local-level respondents, but their counterpart agencies at the national level are not considered influential by policymakers there. Contrary to the hyper-politicized nature of climate change adaptation at international levels, Ghana's policy regime would benefit from increased participation from political agents, as well as from traditional authorities and farmers. These actor groups can help reverse the a-political nature of the adaptation regime, improve power pluralism across actor groups and levels, and facilitate cross-level cooperation between formal and informal institutions crucial to adaptation success.